2013
DOI: 10.1177/0748233713498443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grapefruit juice on amiodarone induced nephrotoxicity in albino rats

Abstract: Amiodarone is a potent antiarrhythmic drug that is used to treat ventricular and supraventricular tachyarrhythmias. The present work studied the effect of amiodarone on the kidney of albino rats and the possible ameliorative role of grapefruit juice. Administration of amiodarone by gastric intubation (18 mg/kg body weight (b.w.), daily for 5 weeks) caused many histological alterations including intertubular leucocytic infiltrations, degeneration of the renal tubules, and atrophy of the glomeruli. Amiodarone ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
5
6
0
Order By: Relevance
“…In the present study, IMI caused a significant decline in the activities of SOD (36.0%), GST (53.7%), GR (30.1%), GPx (50.2%) and CAT (36.0%) after repeated oral administrations in rats for 28 days ( Table 2 ). Similar results have also been observed following subacute exposure of deltamethrin [ 42 ], cypermethrin [ 51 ] and acetamiprid [ 52 ].…”
Section: Resultssupporting
confidence: 82%
“…In the present study, IMI caused a significant decline in the activities of SOD (36.0%), GST (53.7%), GR (30.1%), GPx (50.2%) and CAT (36.0%) after repeated oral administrations in rats for 28 days ( Table 2 ). Similar results have also been observed following subacute exposure of deltamethrin [ 42 ], cypermethrin [ 51 ] and acetamiprid [ 52 ].…”
Section: Resultssupporting
confidence: 82%
“…Urea and creatinine concentration was significantly increased in cypermethrin -treated group compared to the control one. Such findings are in agreement with that reported in other studies (Yousef et al 2003;Saxena and Saxena, 2010y;Sankar et al, 2012 ;Sakr and Albarakai, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…An increase in hepatic carbohydrates, proteins and DNA was observed in rats given and AlCl 3 plus grapefruit. These results are in line with the report of [36] and [37] who reported that grapefruit juice restores the renal contents of carbohydrates and proteins to normal contents. [13] reported that rats were given grapefruit juice prior to treatment with aflatoxin-B 1 resulted in a noticeable reduction of DNA damage in the liver.…”
Section: Discussionsupporting
confidence: 93%